(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
The work “Devonu lugotit Turk” contains ancient legends and tales related to the history of the Turkic peoples, about 300 proverbs and sayings, wise words and more than 700 lines of poetry. About 150 lines of the poetic fragments presented in "Devon" are masnavi, qasida, ghazal and continental fragments of the "bayt" type typical of poetry of the Islamic period, and the author calls them "bayt". The songs in "Devon" are more in the nature of war chronicles, and some large poetic pieces are conditionally called "War War with the Tanguts", "War War with the Uighurs", "War War with the Yabaku"